TCR-Like CAR-T Cells Targeting MHC-Bound Minor Histocompatibility Antigens - Akatsuka, Yoshiki (Frontiers in Immunology, 2020)
Minor histocompatibility antigens (mHAgs) in allogeneic hematopoietic stem cell transplantation are highly immunogenic as they are foreign antigens and cause polymorphism between donors and recipients. Adoptive cell therapy with mHAg-specific T cells may be an effective option for therapy against recurring hematological malignancies following transplantation. Genetically modified T cells with T cell receptors specific to mHAgs have been developed, but formation of mispaired chimeric TCRs between endogenous and exogenous TCR chains may compromise their function. An alternative approach is the development of chimeric antigen receptor (CAR)-T cells with TCR-like specificity whose CAR transmembrane and intracellular domains do not compete with endogenous TCR for CD3 complexes and transmit their own activation signals. However, it has been shown that the recognition of low-density antigens by high-affinity CAR-T cells has poor sensitivity and specificity. This mini-review focuses on the potential for and limitations of TCR-like CAR-T cells in targeting HLA-bound peptide antigens, based on their recognition mechanisms and their application in targeting mHAgs.